Fiscal stimulus in an expectation driven liquidity trap - Joep Lustenhouwer (Bamberg University, Bamberg Economic Research Group (BERG), 2018)
I study expectation driven liquidity traps in a model were agents have finite planning horizons and heterogeneous expectations. There are backward-looking agents, who base their expectations on past observations, and forward-looking agents, who observe the expectations of backward-looking agents, and use model equations within their planning horizon to make forecasts. Expectation driven liquidity traps arise when the presence of backward-looking agents leads to a wave of pessimism after a single, non-persistent, negative preference shock. I find that fiscal stimulus in the form of an increase in government spending or a cut in consumption taxes can be very effective in mitigating the liquidity trap. Moreover, an adequate response of these measures is found to always be able to prevent deflationary spirals, that can arise when there is a large fraction of backward-looking agents with a longer planning horizon. A positive in ation target furthermore reduces the fiscal stimulus required to resolve a liquidity trap for any given size of the negative preference shock. In contrast fiscal stimulus in the form of labor tax cuts is deflationary and hardly effective in mitigating liquidity traps.
Keywords: 330